2000
DOI: 10.1002/1096-9071(200007)61:3<367::aid-jmv15>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Profound suppression of hepatitis B virus replication with lamivudine

Abstract: The therapeutic goals in chronic hepatitis B are to prevent or decrease cirrhosis and hepatocellular carcinoma in patients with pre-cirrhotic or early cirrhotic disease and to stabilise patients with end-stage cirrhosis. Lamivudine is an oral nucleoside analogue that suppresses hepatitis B virus (HBV) replication, and so may achieve both these treatment objectives. The active 5'-triphosphate metabolite of lamivudine has two modes of viral suppression. First, it mimics deoxycytidine triphosphate and is incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…Previous studies of interferon or lamivudine treatment of CHB had suggested that patients who had achieved HBeAg seroconversion had lower baseline serum HBV DNA levels and higher baseline serum ALT levels compared with those patients who did not seroconvert [15,39]. The results for peginterferon alfa2a in these 2 clinical trials support the findings of an earlier study which reported that low viral load (odds ratio 1.6 [1.3-1.8], P = 0.009) and high baseline ALT levels (odds ratio 1.1 [1.0-1.2], P = 0.02) were also predictive of seronconversion in HBeAg-positive patients treated with peginterferon alfa-2b alone or in combination with lamivudine [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of interferon or lamivudine treatment of CHB had suggested that patients who had achieved HBeAg seroconversion had lower baseline serum HBV DNA levels and higher baseline serum ALT levels compared with those patients who did not seroconvert [15,39]. The results for peginterferon alfa2a in these 2 clinical trials support the findings of an earlier study which reported that low viral load (odds ratio 1.6 [1.3-1.8], P = 0.009) and high baseline ALT levels (odds ratio 1.1 [1.0-1.2], P = 0.02) were also predictive of seronconversion in HBeAg-positive patients treated with peginterferon alfa-2b alone or in combination with lamivudine [26].…”
Section: Discussionmentioning
confidence: 99%
“…1 Because of its profound suppression of HBV replication resulting in significant histologic improvement, lamivudine is commonly used as a treatment of chronic HBV infection. [2][3][4] However, in 14% to 32% of patients, a 1-year treatment regimen of lamivudine 100 mg daily is associated with mutation of the tyrosine, methionine, aspartate, aspartate (YMDD) motif in the C domain of the HBV DNA polymerase gene, corresponding to the amino acid codon 552 of the HBV. 2,3 The number of patients with YMDD mutation is higher with prolonged use of lamivudine.…”
mentioning
confidence: 99%
“…This drug is widely used as part of the treatment of HIV infection and has also been used in the treatment of HBV infection (Dienstag et al 1995, Lai & Yuen 2000, Leung 2004). The serum HBV DNA decrease due to lamivudine treatment is frequently accompanied by significant histological and biochemical improvement (Loriot et al 1992).…”
mentioning
confidence: 99%
“…The resistance in the YMDD motif occurs by replacement of the methionine residue at position 550 by either valine (M550V) or isoleucine (M550I). The M550V variant may be accompanied by a mutation that changes leucine into methionine at residue 526 (L526M) (Lai & Yuen 2000, Leung 2004). Such mutations have notably been reported in studies performed with HIV-HBV co-infected patients (Dore et al 1999, Thibault et al 1999, Hoff et al 2001).…”
mentioning
confidence: 99%